International Faust studies : adaptation, reception, translation - Fitzsimmons, Lorna, 1957- (Continuum reception studies series., 2008)
This major interdisciplinary collection captures the vitality and increasingly global significance of the Faust figure in literature, theatre and music. Bringing together scholars from around the world, International Faust Studies examines questions of adaptation, reception and translation centering on Faust discourse in a diversity of cultural contexts, including the Chinese, Japanese, Indian, African, Brazilian and Canadian, as well as the European, British and American. It broadens the field by including studies of lesser known or neglected Faust discourse, including the translation of Goet.